2022
DOI: 10.1111/ene.15635
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of non‐ergot dopamine‐receptor agonists as an adjunct to levodopa in advanced Parkinson's disease: A network meta‐analysis

Abstract: Background and purpose Non‐ergot dopamine agonists (NEDAs) have been used as an adjunct therapy to levodopa in advanced Parkinson's disease (PD) for many years. However, there is no strong evidence that a given NEDA is more potent than another. To compare and rank the efficacy, tolerability, and safety of six commonly used NEDAs as an adjunct to levodopa in advanced PD, which includes long‐acting and standard formulations, a network meta‐analysis was performed. Methods The MEDLINE, Embase, Cochrane Central Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…The low ranking of pramipexole ER might be resulted from the fact that our analysis included only one relevant RCT, which showed that pramipexole ER had lower efficacy than pramipexole 52 . For rotigotine transdermal patch, our result was inconsistent with previous NMA studies in terms of relative efficacy ranking to ropinirole 10 , 13 . The discrepancy may be caused by SP511 study, which was included only in the present study (Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The low ranking of pramipexole ER might be resulted from the fact that our analysis included only one relevant RCT, which showed that pramipexole ER had lower efficacy than pramipexole 52 . For rotigotine transdermal patch, our result was inconsistent with previous NMA studies in terms of relative efficacy ranking to ropinirole 10 , 13 . The discrepancy may be caused by SP511 study, which was included only in the present study (Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…This study showed great improvement in the active arms and in the placebo arm, so there were no significant differences between the drugs and placebo. Some other included studies were different between the present and previous studies 10 , 13 ; nevertheless, in all three NMA studies, pramipexole and ropinirole ER ranked higher, suggesting the robustness of the findings of the present analysis.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…A comparison of the efficacy between ropinirole and rotigotine patches has not yet been conducted. A more recent systematic review and network meta‐analysis evaluating the comparative efficacy of non‐ergot dopamine agonists showed that the improvement rate of UPDRS part II + III was higher with immediate‐ or prolonged‐release ropinirole tablets than with rotigotine 6 . Moreover, a comparative study of ropinirole transdermal patches versus tablets revealed no significant differences in motor or sleep scores 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A more recent systematic review and network meta-analysis evaluating the comparative efficacy of non-ergot dopamine agonists showed that the improvement rate of UPDRS part II + III was higher with immediate-or prolonged-release ropinirole tablets than with rotigotine. 6 Moreover, a comparative study of ropinirole transdermal patches versus tablets revealed no significant differences in motor or sleep scores. 7 In our patient, the dosage of rotigotine was low and other anti-parkinsonian medications were not consistent when each using ropinirole patch and rotigotine.…”
Section: A S E Rep Ortmentioning
confidence: 98%